Exopolysaccharides metabolism and cariogenesis of Streptococcus mutans biofilm regulated by antisense vicK RNA. Issue 1 (31st December 2023) - Sun, Yuting; Chen, Hong; Xu, Mengmeng; He, Liwen; Mao, Hongchen; Yang, Shiyao; Qiao, Xin; Yang, Deqin
ABSTRACT: Background: Streptococcus mutans ( S. mutans ) is a pivotal cariogenic pathogen contributing to its multiple virulence factors, one of which is synthesizing exopolysaccharides (EPS). VicK, a sensor histidine kinase, plays a major role in regulating genes associated with EPS synthesis and adhesion. Here we first identified an antisense vicK RNA (AS vicK ) bound with vicK into double-stranded RNA (dsRNA). Objective: This study aims to investigate the effect and mechanism of AS vicK in the EPS metabolism and cariogenesis of S. mutans . Methods: The phenotypes of biofilm were detected by scanning electron microscopy (SEM), gas chromatography-mass spectrometery (GC-MS), gel permeation chromatography (GPC), transcriptome analysis and Western blot. Co-immunoprecipitation (Co-ip) assay and enzyme activity experiment were adopted to investigate the mechanism of AS vicK regulation. Caries animal models were developed to study the relationship between AS vicK and cariogenicity of S. mutans. Results: Overexpression of AS vicK can inhibit the growth of biofilm, reduce the production of EPS and alter genes and protein related to EPS metabolism. AS vicK can adsorb RNase III to regulate vicK and affect the cariogenicity of S. mutans . Conclusions: AS vicK regulates vicK at the transcriptional and post-transcriptional levels, effectively inhibits EPS synthesis and biofilm formation and reduces its cariogenicity in vivo .